2017
DOI: 10.1007/s00606-017-1451-6
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning up the grasses dustbin: systematics of the Arundinoideae subfamily (Poaceae)

Abstract: Among the 12 subfamilies currently considered in the systematics of Poaceae, the Arundinoideae have long been considered as a dustbin group, with a diversity of forms putatively hiding incertae sedis. Because this subfamily has been poorly investigated using molecular markers for the last two decades, the present study provides the first complete phylogeny of the Arundinoideae based on five plastid DNA loci sequenced for 12 genera, and analysed with and without plastome data from previous studies. The refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Tribe Molinieae Jirásek has a mean stem and crown age of 40.93 and 7.08 Ma. This crown age is younger than the 15 Ma age found in Hardion et al (2017), but that study noted a similarly long stem for this group and argued for a possible East Asian origin of its three or four genera. In our biogeographical analysis, the stem area is Afrotropical (50%), and the probable crown area is Cosmopolitan (68%).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Tribe Molinieae Jirásek has a mean stem and crown age of 40.93 and 7.08 Ma. This crown age is younger than the 15 Ma age found in Hardion et al (2017), but that study noted a similarly long stem for this group and argued for a possible East Asian origin of its three or four genera. In our biogeographical analysis, the stem area is Afrotropical (50%), and the probable crown area is Cosmopolitan (68%).…”
Section: Discussioncontrasting
confidence: 50%
“…and Crinipes Hochst. (four species) (Teisher et al, 2017; Hardion et al, 2017). Hardion et al (2021) found close relationships to Crinipes for two potentially extinct monotypic genera, Leptagrostis C.E.Hubb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our 2017 classification, we have added two tribes, 22 new or resurrected subtribes, and rearranged the basal split in the PACMAD clade. Tribe Crinipedeae (Hardion et al, 2017) is accepted here (previously it was treated as subtribe Crinipinae in Molinieae) since Leptagrostis C. E. Hubb. and Piptophyllum C. E.…”
Section: Resultsmentioning
confidence: 99%
“…Kellogg () accepted 18 genera plus “ Eragrostis walteri Pilg.” [= Pratochloa walteri (Pilg.) Hardion] without subtribe affiliation (Hardion et al, in press). Soreng et al (2015b) placed Alloeochaete, Danthonidium , and Phaenanthoecium in the Danthonioideae but also included Moliniopsis in the Arundineae and reported that “ Eragrostis walteri ” belonged in the Arundinoideae.…”
Section: Discussionmentioning
confidence: 99%